The Revolt of the Crew of De Zeven Provincien and the Activities of the National Movement of 1930-1933 - Akbar, Muh; Aman, Aman (Universitas Negeri Padang, 2023)
World history records that at the end of 1920, the global community was hit by a very dramatic economic depression, which resulted in protests by the people as a result of cuts in the wages of civil servants in all circles, both Dutch and Indigenous nationalities, by 17%, wage cuts were part of the efforts government to reduce the gap between government revenues and spending when the economic depression has caused government revenues in an emergency. The relationship between the rebellion of the Crew of De Zeven Provincien and the activities of the national movement during the reign of Governor-General Jhr. B.C. De Jonge. After the uprising immediately, the Dutch East Indies government, under the leadership of Governor-General Jhr. B.C. De Jonge carried out reactionary and violent politics against the activities of the national movement. Movement organizations were increasingly under pressure from the colonial government, and some radical and revolutionary movement figures were even arrested. The research method used is the historical method, namely heuristics, source criticism, interpretation, and historiography, and this research uses library research where the researcher examines several sources related to this research. Thus, it can be concluded that in the De Zeven Provincien Crew Mutiny in 1933, Governor General Jhr. B.C. De Jonge put more pressure on the national movement organization in Indonesia.